Optimization of design for better structural capacity - Belgasmia, Mourad, 1973- (IGI Global, 2019)
"This book explores how to overcome structural failures and guarantee a long life and go to tap hidden structural capacities, by touching different axes in field of civil engineering by optimizing the design, like pre-dimensioning dampers and fire design and optimizing both structural model and implementation by adding the dashpot and changing the manner of programming"--